Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2478/s11536-013-0240-z
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Reynolds Risk Score in men with stable angina

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Pietka et al . ( 21 ) in a cohort of 119 non-diabetic men with stable coronary artery disease and preserved left ventricular systolic function showed that men with higher RRS had lower frequency of marginal or no atherosclerotic coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Pietka et al . ( 21 ) in a cohort of 119 non-diabetic men with stable coronary artery disease and preserved left ventricular systolic function showed that men with higher RRS had lower frequency of marginal or no atherosclerotic coronary arteries.…”
Section: Discussionmentioning
confidence: 99%